Validity and validation in archetype analysis: practical assessment framework and guidelines. (8th February 2022) - Piemontese, Luigi; Neudert, Regina; Oberlack, Christoph; Pedde, Simona; Roggero, Matteo; Buchadas, Ana; Martin, Dominic A; Orozco, Richard; Pellowe, Kara; Segnon, Alcade C; Zarbá, Lucía; Sietz, Diana
Abstract: Archetype analysis is a promising approach in sustainability science to identify patterns and explain mechanisms shaping the sustainability of social-ecological systems. Although considerable efforts have been devoted to developing quality standards and methodological advances for archetype analysis, archetype validation remains a major challenge. Drawing on the insights from two international workshops on archetype analysis and on broader literature on validity, we propose a framework that identifies and describes six dimensions of validity: conceptual; construct; internal; external; empirical; and application validity. We first discuss the six dimensions in relation to different methodological approaches and purposes of archetype analysis. We then present an operational use of the framework for researchers to assess the validity of archetype analysis and to support sound archetype identification and policy-relevant applications. Finally, we apply our assessment to 18 published archetype analyses, which we use to describe the challenges and insights in validating the different dimensions and suggest ways to holistically improve the validity of identified archetypes. With this, we contribute to more rigorous archetype analyses, helping to develop the potential of the approach for guiding sustainability solutions.